2022
DOI: 10.1007/s00339-022-05396-1
|View full text |Cite
|
Sign up to set email alerts
|

Modified copper zinc ferrite nanoparticles doped with Zr ions for hyperthermia applications

Abstract: The problem of the present work is to synthesize a nanomagnetic material with low TC below 45 °C and its particle size below 30 nm to be appropriate material for convert magnetic loss into heat energy. A series of Cu0.4Zn0.6+yZryFe2–2yO4 nanoparticles compositions where y = (0.05, 0.1) were synthesized via citrate sol–gel method. The prepared samples were characterized by X-ray diffraction (XRD) and transmission electron microscopy (TEM). The grains were observed from SEM confirming the crystalline structure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…Several other types of magnetic nanoparticles have also been utilized in magnetic hyperthermia including iron, 46 magnesium alloys, 79 Ni alloys, 80 Ni-Cr alloy, 81 Ni-Si and Ni-Al, 82 Fe-Ni alloys, 83 Fe-Co alloy, 47 FeNiCo alloys, 84 Ni-Cu alloys, 85,86 Fe-Al alloy, 87 Fe-Au alloys, 88,89 Fe 3 C nanoparticles, 71 Fe-Cr-Nb-B alloy, 90 Fe–Mn–Gd ferrite, 91 hematite (α-Fe 2 O 3 ) and nickel ferrite, 92 cobalt ferrite, 93–105 cobalt zinc ferrite, 106111 Zn‐Mg ferrite, 112 Mg 0.7 Zn 0.3 Fe 2 O 4 nanocrystals, 113 manganese ferrite , 44,114118 ZnMn ferrite, 119124 magnesium ferrite, 125128 zinc ferrite, 45,129133 Zn–Ni spinel ferrite, 134 Zn-doped spinel Fe 3 O 4 , 135 nickel ferrite, 136 copper ferrite, 137 copper zinc ferrite, 138 and γ-Fe 2 O 3 . 139144…”
Section: Nanoparticles Used In Magnetic Hyperthermiamentioning
confidence: 99%
“…Several other types of magnetic nanoparticles have also been utilized in magnetic hyperthermia including iron, 46 magnesium alloys, 79 Ni alloys, 80 Ni-Cr alloy, 81 Ni-Si and Ni-Al, 82 Fe-Ni alloys, 83 Fe-Co alloy, 47 FeNiCo alloys, 84 Ni-Cu alloys, 85,86 Fe-Al alloy, 87 Fe-Au alloys, 88,89 Fe 3 C nanoparticles, 71 Fe-Cr-Nb-B alloy, 90 Fe–Mn–Gd ferrite, 91 hematite (α-Fe 2 O 3 ) and nickel ferrite, 92 cobalt ferrite, 93–105 cobalt zinc ferrite, 106111 Zn‐Mg ferrite, 112 Mg 0.7 Zn 0.3 Fe 2 O 4 nanocrystals, 113 manganese ferrite , 44,114118 ZnMn ferrite, 119124 magnesium ferrite, 125128 zinc ferrite, 45,129133 Zn–Ni spinel ferrite, 134 Zn-doped spinel Fe 3 O 4 , 135 nickel ferrite, 136 copper ferrite, 137 copper zinc ferrite, 138 and γ-Fe 2 O 3 . 139144…”
Section: Nanoparticles Used In Magnetic Hyperthermiamentioning
confidence: 99%
“…UV-Vis analysis was employed to explore the optical properties of the synthesized Ni-Zn nanoparticles, including both undoped and Cu-doped Ni-Zn ferrite nanoparticles. The analysis aimed to determine the bandgap energy (Eg) using the maximum transmittance wavelength, according to the equation Eg = 1240/λ max (in eV) [14]. The obtained UV-Vis spectra provided insights into the absorption behaviour of the samples across the ultraviolet and visible regions of the electromagnetic spectrum.…”
Section: Uv-vis Analysismentioning
confidence: 99%
“…According to Shirsath et al, the saturation magnetization decreased with the substitution of Fe +2 by Co +2 Li 0.5 Fe 2.5 O 4 . Salem et al discovered the substitution of Fe with Zr ions in modified copper zinc ferrite compounds and found that the material exhibited a magnetic hysteresis loop typical of soft ferrite . The substance turns into a superparamagnetic substance at higher Zr contents .…”
Section: Introductionmentioning
confidence: 99%
“…15 Salem et al discovered the substitution of Fe with Zr ions in modified copper zinc ferrite compounds and found that the material exhibited a magnetic hysteresis loop typical of soft ferrite. 16 The substance turns into a superparamagnetic substance at higher Zr contents. 16 MgFe 2 O 4 is one of the most studied ferrite materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation